ANALISIS SIMBOL NONVERBAL PADA TRADISI MAKAN DALAM KELAMBU MASYARAKAT BUGIS DESA PUNGGUR KAPUAS KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA (PENDEKATAN SEMIOTIK) - Ria Yuliani (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2023)
"Indonesia is known as a country that has rich cultural, ethnic and religious diversity. Each culture has traditions that are adhered to and practiced, and each tradition has a unique meaning. Punggur Kapuas Village, Sungai Kakap District, Kubu Raya District, is one example a multicultural village known for its diversity of tribes, cultures and traditions. One of the tribes in the village is the Bugis tribe, with various traditions, including the tradition of eating in mosquito nets. The tradition of eating in mosquito nets is carried out with the aim of honoring deceased ancestors and maintain the customs and habits of Bugis ancestors in ancient times. There are two types of traditions of eating in mosquito nets, namely the tradition of eating in mosquito nets before marriage and the tradition of eating in mosquito nets in the procession of swinging. This study aims to describe the nonverbal symbols and processions contained in the tradition eating in mosquito nets for the Bugis community in Punggur Kapuas Village, Sungai Kakap District, Kubu Raya Regency. This study uses a descriptive approach with qualitative research methods. Data collection techniques used include observation, interviews, and documentary studies. The data collection instruments used were observation guides, interview guides, and documentation. The validity of the data was checked through source triangulation and theory triangulation. Data analysis uses an interactive data analysis model with a semiotic approach. The results of this study revealed the tradition of eating in mosquito nets in Punggur Kapuas Village, Sungai Kakap District, including the procession of eating in mosquito nets, the shape of the symbols, and the meaning of the tools or objects used in the tradition of eating in mosquito nets."